A part of discovery expanding the promise of medicine: handbook of ocular surface treatment - Rao, Srinivas Kamalakara; Cheng, Huei-Chan; Mohd. Kamal, Khairidzan; Lim, Li; Zuguo, Liu; Padilla, Ma Dominga; Puangsricharern, Vilavun; Jong-Suk, Song; Young, Alvin (Allergan, 2015)
A variety of disease processes can impact on the anatomy and function of the Ocular Surface. These can result in either simple, irritative symptomatology or more severe, incapacitating problems for the patient-resulting in sign icant morbidity and or loss of work efficiency and productivity. Such symptomatology can also be accompanied by changes in the structures of the eye with permanent sequelae - if not treated in a timely and appropriate manner.